Mutação constitucional: dos contornos doutrinários e jurisprudenciais pátrios - Júlia Cristina de Souza Soares (2022)
The present research approaches the figure of the constitutional change in Brazil, in the doctrinal scopes and of the jurisprudence of the Federal Supreme Court, using bibliographical methodology of qualitative, quantitative, descriptive and exploratory nature. It is intended to verify the existence (or not) of a gap between what the national doctrine and the STF understand by constitutional change, especially in the identification of cases. To this end, we initially seek to outline the patriotic doctrinal contours of the figure, from the importation of the concept, in 1987, until mid-2018. Continuously, through qualitative and quantitative research on the Supreme website, it is verified which meanings the STF has been attributing mutations in its decisions to the figure. Further on, with the aim of identifying the existence (or not) of a gap between what the STF and the national doctrine understand by constitutional change, especially in the identification of cases, a jurisprudential analysis - quantitative and qualitative - of the judgments is carried out cited by Brazilian scholars as examples of authentic constitutional change. At this stage, we analyze which argumentative paths were traced by the Ministers of the Federal Supreme Court when judging the cases cited by national doctrine as examples of authentic constitutional changes. Finally, in view of the results achieved, we seek to make reflections - initial and not exhaustive - on the figure of constitutional change in the functional and normative fields, and their real indispensability as a category, in the Brazilian context. In the end, given the absence of a structured concept that is supported in normative terms and the patent rhetorical and random use of the figure by the Supreme, under the functional prism, it is concluded that, in the current doctrinal and jurisprudential context of the country, there is no foundation or justification that guarantees the survival of the thesis of constitutional change, which, in itself, indicates its dispensability as a category, in the terms outlined by Pedron (2012).